Do managers and employees perceive motivating factors differently in Malaysia? - Islam, Rafikul; Ahmed, Selim (Inderscience Enterprises Ltd., 2014)
Employee motivation is crucial for sustainable growth of any organization. Highly motivated employees contribute significantly to an organization’s bottomline and its overall productivity. It is a primary task of the managers to know the motivating factors of their employees and act accordingly so that the organization can remain competitive in the marketplace. The main objective of the present research is to investigate the difference, if any, between the perceptions of managers and employees on a pre-determined set of motivating factors. As it has been shown, though overall, they were in agreement, but they do differ on certain fundamental issues in terms of ranking of the above-mentioned set of motivating factors. Impact of the respondents’ demography on the findings, in the Malaysian context, is also highlighted. This research underscores the importance of the knowledge of employee motivating factors before developing or dealing with any motivational program in an organization.